2015
DOI: 10.1097/ccm.0000000000001260
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind Prospective Randomized Controlled Trial of Dopamine Versus Epinephrine as First-Line Vasoactive Drugs in Pediatric Septic Shock

Abstract: Dopamine was associated with an increased risk of death and healthcare-associated infection. Early administration of peripheral or intraosseous epinephrine was associated with increased survival in this population. Limitations should be observed while interpreting these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(99 citation statements)
references
References 47 publications
2
87
0
10
Order By: Relevance
“…In another study470 comparing adrenaline and dopamine, adrenaline was associated with a lower rate of mortality than dopamine. Potential risks include a tendency for dopamine to exacerbate inflammation, and adrenaline was linked to hyperglycemia and persistent hyperlactatemia.…”
Section: Cq19: Pediatric Considerationsmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study470 comparing adrenaline and dopamine, adrenaline was associated with a lower rate of mortality than dopamine. Potential risks include a tendency for dopamine to exacerbate inflammation, and adrenaline was linked to hyperglycemia and persistent hyperlactatemia.…”
Section: Cq19: Pediatric Considerationsmentioning
confidence: 94%
“…One RCT470 reported that adrenaline use in pediatric patients with sepsis was associated with a lower mortality rate in comparison to dopamine470 and recommended adrenaline as a first‐line drug therapy. However, this was a single center study with 120 participants, and it is necessary to recognize that the design of this study weakens it as an evidentiary basis for the use of adrenaline as a first‐line drug.…”
Section: Cq19: Pediatric Considerationsmentioning
confidence: 99%
“…Dopamine therapy, in particular the first-line agent used in the study center, has been shown to lead to decreased end-organ perfusion, failure to restore cerebral autoregulation, and failure to increase cerebral perfusion in the setting of increased BP [19,26,34,35,36]. In adult and pediatric data, dopamine use as compared to norepinephrine or epinephrine therapy leads to higher mortality rates [37,38]. A possible mechanism may be that while dopamine increases BP, it has been shown to decrease left ventricular output which may lead to increased strain on the myocardium and decreased oxygen delivery despite improved BP [36,39].…”
Section: Discussionmentioning
confidence: 99%
“…Six of these studies were underpowered to find a difference based on their observed versus stated expected mortality rate (8;1618;22;29). Three of the 14 studies demonstrated a statistically significant difference in their primary outcome between study groups (23;25;31). None of the studies in which mortality was a primary outcome provided data on cause of death, reflecting the common intent to measure all-cause mortality.…”
Section: Resultsmentioning
confidence: 99%
“…The study interventions were classified as drug-related in nine trials (47%) (9;1623), practice-related in seven (37%) (8;2429) and device-related in three (15%) (30–32). The control group was a placebo in nine trials (47%) (9;1623) and usual care in 8 trials (42%) (8;2429). In the remaining two trials (11%) (31;32) it was unclear whether or not the control group represented usual care.…”
Section: Resultsmentioning
confidence: 99%